The Influence of Profitability, Leverage, and Company Size on Tax Avoidance In Manufacturing Companies (Period 2018-2022) - Pujia, Dede Puspa; Hidayat, Cecep Edi; Kamela, Hurian; Susilowati, Susilowati; Prabusakti, Rengga (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research aims to analyze the influence of profitability, leverage and company size on Tax Avoidance in manufacturing companies for the period 2018 - 2022. This research is quantitative with a research sample of 11 companies. The data analysis method uses multiple linear regression analysis using SPSS version 25. The results of this research reveal that profitability has a negative effect on tax avoidance. Meanwhile, leverage and company size have no effect on tax avoidance.